Prospective implications of insufficient sleep for athletes - Riegler, K. E.; Guty, E. T.; Thomas, G. A.; Bradson, M. L.; Arnett, P. A. (Journal of Athletic Training, 2023)
Context Poor sleep is common in collegiate student-athletes and is associated with heterogeneous self-reported complaints at baseline. However, the long-term implications of poor sleep at baseline have been less well studied.